Effects of in-grain misorientation developments in sensitization of 304 L austenitic stainless steels. (24th October 2018) - Srinivasan, N; Kumaran, S Senthil; Venkateswarlu, D
Abstract: This paper focussed on sensitization behaviour of cold rolled (CR) and warm rolled (WR) of AISI 304 L austenitic stainless steels. The main aim of this study was to mitigate sensitization issues of austenitic stainless steels. All the specimens were given two different heat treatment of 675 °C 6 h and 675 °C 5 h. The electron backscattered diffraction (EBSD) measurements were revealed developments of in-grain misorientations and types of grain boundary statistics. An EBSD system along with a suitable computer algorithm was used to quantify in-grain misorientations called near boundary gradient zone (NBGZ). The microstructures that contained quantifiable zones of in-grain misorientations exhibited low value of degree of sensitization (DOS) for 5% and 10% rolled specimens. DOS was assessed by double loop electrochemical potentiokinetic reactivation (DL-EPR) test. It was established that low value of DOS for the specimens of 5% and 10% rolled provided diffusion short-cuts or high diffusivity paths for Chromium that improved resistance to sensitization. A slight pre-strain and subsequent annealing failed to increase population of special boundaries. The visible grain fragmentation accelerated carbide precipitation and decreased resistance to sensitization. The sensitized specimens after DL-EPR test subjected to white light interferometry (WLI) measurements that revealed grain boundary depth information. The combined data set of EBSD + WLI provided linkage between grain boundary depth and in-grain misorientations.